Empirical Analysis of the Reality of Gender Inclusiveness of Participatory Forest Management Regime - Saguye, Tesfaye S (American Journal of Human Ecology, 2017)
The Conventional forest management system and practice have failed to improve the forest condition as well as to sustainably address the livelihood of the local community. In recognition of continued deforestation, degradation and loss of biodiversity associated with the mainstream  “fences and fines’’ forest management system a new regime has practiced in a few national forest priority areas since 1990s, emphasizing the need to incorporate the aspiration of local people in forest conservation strategies in Ethiopia. The main purpose of this study was to analyze the reality of gender inclusiveness of the newly introduced forest management system. Both qualitative and quantitative methods of data collection particularly, semi-structured questionnaire survey, focus group discussions and key informant interviews were employed. Analysis of the data reveals that participatory forest management process in the study area was women’s exclusionary in reality even from the lowest nominal typology of participation to the highest in hierarchy of participation, interactive and empowerment in entire participatory forest management process. The study also identified the exclusionary factors which are constraining gender participation such as exclusionary membership rules, gender division of labour, poor educational back grounds, and poor enactment of already established rules and so on.